Hubungan antara Teman Sebaya dengan Motivasi Belajar pada Siswa SMP Negeri 2 Sunggal Kelas IX-1 Tahun 2021. - Ozi Zulfani Surbakti; Nurmaida Irwani Siregar (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aimed to obtail information and clarity on the relationship between in tercourse peer motivation with eighth grade students of junior high school Negeri 2 Sunggal class IX-1 at year 2021. The method use is likert scale the method data analitys used is product moment corellation. Based on the date r anality, product moment with coofisien = 0,324 and determinan coofisien 2 = 0,413 with P =0,0010,050. The result of the study showed that this hipotesis is accepted it showed that there are correlation between association peer reind study motivation. Is equetion, it means if association peer highost so that motivation. Data collection tools in this study was a questionaire. The result of data showed that association peer is 41,3% by hipotetic mean = 100 and empiries mean = 111,17, its over deviation standart = 11,049 and study motivation in high category by mean hipotetic = 100 and empiries mean= 115,80 and its over deviation standart=14,163. It means that the hypothesis is that the higher the good relationship between peers, the higher the motivation to learn.